GmAGL1, a MADS-Box Gene from Soybean, Is Involved in Floral Organ Identity and Fruit Dehiscence - Chi, Yingjun; Wang, Tingting; Xu, Guangli; Yang, Hui; Zeng, Xuanrui; Shen, Yixin; Yu, Deyue; Huang, Fang (Frontiers in Plant Science, 2017)
MADS-domain proteins are important transcription factors involved in many aspects of plant reproductive development. In this study, a MADS-box gene, Glycine max AGAMOUS-LIKE1 (GmAGL1), was isolated from soybean flower. The transcript of GmAGL1 was expressed in flowers and pods of different stages in soybean and was highly expressed in carpels. GmAGL1 is a nucleus-localized transcription factor and can interact directly with SEP-like proteins in soybean flowers. Ectopic overexpression of GmAGL1 resulted in the absence of petals in Arabidopsis. Moreover, morphological changes in the valves were observed in 35S:GmAGL1 Arabidopsis fruits that dehisced before the seeds reached full maturity. GmAGL1 was found to be sufficient to activate the expression of Arabidopsis ALC, IND, STK, SEP1 and SEP3. Therefore, our data suggest that GmAGL1 may play important roles in both floral organ identity and fruit dehiscence.